Estudio de la calidad espermática de muestras de la cola del epidídimo de cobayos y evaluación de tres diluyentes a base de leche descremada - Paccha Chamba, José Antonio (2023)
The guinea pig is a species that requires studies to improve its reproductive efficiency. The aim of the present study was to determine sperm quality in guinea pigs, verify the influence of diet and evaluate three skim milk-based extenders. We carried out three experiments. In experiment 1, we evaluated sperm concentration and morphology in guinea pigs of eight and older than ten weeks of age (n=35). In experiment 2, the influence of two diets with 32 and 40% neutral detergent fiber (NDF) was evaluated over sperm quality and testicular parenchyma development in guinea pigs (n=20). In experiment 3, we analyzed sperm cell motility and vigor from 0 to 240 minutes, comparing three skim milk-based extenders. Descriptive statistics, ANOVA, and repeated measures analysis were used. Also a protected t-test to compare means was used. In experiment 1, age influenced sperm quality, 8-week-old guinea pigs presented a higher (p ≤ 0.05) percentage of morphological defects. In experiment 2, we found higher percentage of sperm cells with morphological defects, and higher (p ≤ 0.05) seminiferous tubule lumen area and perimeter in guinea pigs fed with 32% NDF. In experiment 3, motility and vigor reduced over time (p < 0.001), but there was no effect of extender (p = 0.20). However, when we used BotuGold® in samples of guinea pigs fed with 32% NDF (p = 0.01), they presented higher sperm cell motility and vigor. In conclusion, age and weight affect guinea pig sperm quality, fiber levels did not affect sperm quality. However, high percentage of starch negatively influenced sperm morphology and testicular epithelium development. BotuGold® extender improves motility and vigor in seminal samples of low sperm quality. Keywords: Spermiogram, guinea pig, seminiferous tubule, Botugold, NDF